2004
DOI: 10.1113/jphysiol.2004.066662
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic plasticity at two giant auditory synapses in normal and deaf mice

Abstract: Large calyceal synapses are often regarded as simple relay points, built for high-fidelity and high-frequency synaptic transmission and a minimal requirement for synaptic plasticity, but this view is oversimplified. Calyceal synapses can exhibit surprising activity-dependent developmental plasticity. Here we compare basal synaptic transmission and activity-dependent plasticity at two stereotypical calyceal synapses in the auditory pathway, the endbulb and the calyx of Held. Basal synaptic transmission was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 58 publications
7
64
2
1
Order By: Relevance
“…Here we describe a balance in MSO neurons between excitatory and inhibitory STP, defined as steady state, kinetics, and recovery from depression. This STP is most likely based on presynaptic factors such as pool depletion (Schneggenburger et al, 1999;Wu and Borst, 1999;Oleskevich et al, 2004;Yang and Xu-Friedman, 2008), Ca 2ϩ current inactivation (Forsythe et al, 1998;Xu and Wu, 2005;Mochida et Xu-Friedman, 2008), since we found no indication of a postsynaptic contribution.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Here we describe a balance in MSO neurons between excitatory and inhibitory STP, defined as steady state, kinetics, and recovery from depression. This STP is most likely based on presynaptic factors such as pool depletion (Schneggenburger et al, 1999;Wu and Borst, 1999;Oleskevich et al, 2004;Yang and Xu-Friedman, 2008), Ca 2ϩ current inactivation (Forsythe et al, 1998;Xu and Wu, 2005;Mochida et Xu-Friedman, 2008), since we found no indication of a postsynaptic contribution.…”
Section: Discussionmentioning
confidence: 67%
“…However, inhibitory vesicles impose a 2-to 3-fold larger conductance than excitatory vesicles, resulting in an equal overall conductance. The conductance imposed by the quantal contents of both inputs is large, comparable to an endbulb-type synapse (Oleskevich et al, 2004;Xu-Friedman and Regehr, 2005). The unusual strength of the inhibitory input speaks to the fundamental importance of inhibition in this circuit (Brand et al, 2002;Pecka et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Redd et al 2000;Lee et al 2003). Subsequent functional assessments have confirmed irregular transmission characteristics (Oleskevich and Walmsley 2002;Oleskevich et al 2004;Manis 2005, 2006).…”
Section: Fig 10mentioning
confidence: 97%